Gender, Transnational Networks and Remittances: Evidence from Germany - Elke Holst; Andrea Schäfer; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Remittances from Germany are substantial. Cross-border transfers to family and friendship networks outside Germany are not only made by foreigners. Many naturalized migrants send money home as well. Here, we focus on transnational networks and gender-specific determinants of remittances from the senders' perspective, based on data from the German Socio-Economic Panel Study (SOEP) for the years 2001-2006.
Keywords: F24; J16; D13; 330; Remittances; Gender; Foreigners; Naturalized Migrants; Rücküberweisungen; Weibliche Arbeitskräfte; Arbeitsmigranten; Geschlecht; Soziales Netzwerk; Deutschland